Complex Effects of Hot and Cold Procedures on Skin Elasticity in Spa & Wellness - Panovska, Nevenka; Dimitrova, Antoaneta (European Scientific Journal, ESJ, 2018)
The purpose of this study is to evaluate the complex effects of the hot and cold procedures, practiced in modern Spa & Wellness, on skin elasticity, as that indicator is an integral factor defining the aesthetic vision of the skin. Material and Methods: The present study tracked 60 women aged 35 to 65 years. The methods included an aesthetic skin rejuvenation program that contained a complex of 12 Spa and Wellness rituals conducted in a period of one month, three times per week. Each treatment was Ð° temperature contrast procedure through a Parafango body thermo-application and a face cryo-gel application. The facial skin condition was assessed by an A-ONE apparatus - an automatic skin diagnostic analyzer. Results: A significant improvement in the skin elasticity in the three studied age groups was observed after the procedures. This indicator increased 3.75 units (9.93%) in the 35-44 age group, 3.5 units (11.36%) in the 45-54 age-group and 1.80 units (8.22 %) in the observed individuals from 55-65 age-group. At the end of a treatment, the increase in all three age groups was statistically significant (p<0.05). Skin elasticity assessment was significantly lower for all three age-groups before the procedures, compared to the established standards. After the applied procedures, the skin elasticity was approaching the established standard (the first age group exceeded the standard, the second approached the standard and the third was slightly below the standard). Conclusion: The study reveals that the complex effects of hot and cold procedures result in improved skin elasticity.